Fast Food Consumption Patterns and Childhood Overweight/Obesity in Dhaka City, Bangladesh (Bangladesh Journal of Nutrition, 2020)
A descriptive cross-sectional study was carried out among 106 school going overweight and obese children (fifty boys and fifty-six girls) selected from four schools of Dhaka city. The aim of this study was to assess the overweight or obesity pattern among the children and their fast-food eating behavior. Samples were selected by simple random sampling during the time frame of September, 2017 to April, 2018. Data Analysis was conducted by using IBM SPSS16.0. The average weight of the school children was 41.54 ± 9.65 kg, average height was 132.2 ± 10.82 cm and average Mid Upper Arm Circumference (MUAC) was 24.83 ± 2.8 cm. It was found that about 28.3% children were overweight, 55.7% children were obese and rest of the children were severely obese. The study revealed that about21.7% children had consumed fast food every day in a week, about 40.6% children had fast-food 2-3 days weekly and28.3% children had fast food 4-5 days in a week. Among the fast food items, Cake/Noodles/Pastry were consumed by76.4% respondents, Chocolate/ Ice-cream by 67.9% respondents, Chips was consumed by 67.0% of the respondents and Burger/Pizza/Sandwich were consumed by 62.3% of the respondents. About 23.6% children preferred having nuggets, 17.9% children sweets, 12.3% children chicken ball and 7.5% children biriyani. It was also shown that about36.8% children had fast-food as tiffin and at evening as snacks. It was observed that fast food eating pattern is highly prevalent among the overweight and obese school going children and this food habit need to be changed in order to prevent diabetes, high blood pressure, arthritis, high cholesterol level at adulthood.Bangladesh J. Nutr. Vol. 33, December 2020, P: 21-27